2005
DOI: 10.1023/b:trop.0000049296.47350.80
|View full text |Cite
|
Sign up to set email alerts
|

Anthelmintic Activity of Extracts of Spondias mombin Against Gastrointestinal Nematodes of Sheep: Studies In Vitro and In Vivo

Abstract: This study was carried out to validate the efficacy of Spondias mombin, used locally as an anthelmintic, and to standardize the effective dose of the plant extract required for worm control in livestock. In vitro and in vivo studies were conducted to determine the direct anthelmintic effect of ethanolic and aqueous extracts of S. mombin towards different ovine gastrointestinal nematodes. A larval development assay (LDA) was used to investigate the in vitro effect of extracts on strongyle larvae. Another study … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
27
0
6

Year Published

2007
2007
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 48 publications
(35 citation statements)
references
References 8 publications
2
27
0
6
Order By: Relevance
“…The study showed high presence of tannins in both leaf and stem bark extracts supporting the strong use of Spondias mombin in healing wounds, various ulcers, frost-bite and burns in traditional herbal medicine (1). The tannins, flavonoids and alkaloids as seen in the results give credence to the reported anti-microbial (24) anti-viral (18), and antihelminthic (25) properties of Spondias mombin.…”
Section: IVsupporting
confidence: 64%
“…The study showed high presence of tannins in both leaf and stem bark extracts supporting the strong use of Spondias mombin in healing wounds, various ulcers, frost-bite and burns in traditional herbal medicine (1). The tannins, flavonoids and alkaloids as seen in the results give credence to the reported anti-microbial (24) anti-viral (18), and antihelminthic (25) properties of Spondias mombin.…”
Section: IVsupporting
confidence: 64%
“…No presente trabalho, observou-se que os animais do grupo G2, tratados com o dobro do tratamento do G1, revelaram potencial anti-helmíntico para três gêneros de nematoides, exceto Haemonchus. Essa não similaridade pode ser consequente à ação de micro-organismos do rúmen ou de determinados compostos sobre os constituintes químicos ativos, por influência na absorção ou solubilidade (ADEMOLA et al, 2005;BATATINHA et al, 2004). A microflora ruminal pode ser responsável pela alteração do metabolismo ou do mecanismo de ação de alguns nutrientes, medicamentos ou materiais bioativos, quando administrados oralmente (VANDAMME; ELLIS, 2004).…”
Section: Concentraçõesunclassified
“…The leaves have also been demonstrated to have antihelminthic (Ademola et al, 2005) and abortifacient (Offiah and Anyanwu, 1989;Nworu et al, 2007) properties. In traditional medical practice of southern Nigeria, the freshly boiled aqueous leaf extract of SM is used to treat dizziness, especially after childbirth, while the bark is used to treat mothers after delivery (Onwuka, 1992).…”
Section: Introductionmentioning
confidence: 99%